Coordination in large-scale agile software development : integrating conditions and configurations in multiteam systems - Scheerer, Alexander (Springer, 2017)
Annotation This volume explores coordination within and between teams in the context of large-scale agile software development, providing readers a deeper understanding of how coordinated action between teams is achieved in multiteam systems. An exploratory multiple case study with five multiteam systems and a total of 66 interviewees from development teams at SAP SE is presented and analysed. In addition, the book explores stereotypes of coordination in large-scale agile settings and shares new perspectives on integrating conditions for coordination.
Keywords: Agile software development.; elektronické knihy; electronic books